Structure-based approach: molecular insight of pyranocumarins against α-glucosidase through computational studies. Issue 6 (25th January 2023) - Abdjan, Muhammad Ikhlas; Aminah, Nanik Siti; Kristanti, Alfinda Novi; Siswanto, Imam; Ilham, Baso; Wardana, Andika Pramudya; Takaya, Yoshiaki
Abstract : We presented the structure-based approach (molecular docking and MD simulation) to understand the dynamics behavior and inhibitory efficiency of pyranocoumarin derivatives against α-glucosidase at the molecular level. Abstract : α-glucosidase is an enzyme that catalyzes the release of α-glucose molecules through hydrolysis reactions. Regulation of this enzyme can increase sugar levels in type-2 diabetes mellitus (DM) patients. Pyranocoumarin derivatives have been identified as α-glucosidase inhibitors. Through an in silico approach, this work studied the inhibition of three pyranocoumarin compounds against the α-glucosidase at the molecular level. Molecular docking and molecular dynamics simulation were performed to understand the dynamics behavior of pyranocoumarin derivatives against α-glucosidase. The prediction of free binding energy (Δ G bind ) using the Quantum Mechanics/Molecular Mechanics-Generalized Born (QM/MM-GBSA) approach for each system had the following results, PC1-α-Glu: −13.97 kcal mol −1, PC2-α-Glu: −3.69 kcal mol −1, and PC3-α-Glu: −13.68 kcal mol −1 . The interaction energy of each system shows that the grid score, Δ G bind, and Δ G exp values had a similar correlation, that was PC1-α-Glu > PC3-α-Glu > PC2-α-Glu. Additionally, the decomposition energy analysis (Δ G residuebind) was carried out to find out the contribution of the key binding residue. The results showed that there were 15 key binding residues responsible for stabilizing pyranocumarin binding with criteria of Δ G residuebind < −1.00 kcal mol −1 . The evaluation presented in this work could provide information on the molecular level about the inhibitory efficiency of pyranocoumarin derivatives against a-glucosidase enzyme based on computational studies.